Universalitas Islam dan Lokalitas Budaya dalam Bingkai Islam Nusantara - Fikri, Ishom Fuadi (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2018)
Islam has both universal and particular dimension, where the universality of Islam is reflected in the maq??id al-shar??ah, i.e. public benefits, whereas the Islamic particularity deals with practical aspects of the Islamic law in the human life, including local cultures. This means that the presence of Islam does not aim to eliminate the human?s cultures, rather it serves as a universal value which is able to permeate and accommodate various local cultures. The universality of Islam and the cultural locality should not be in, somehow, an opposite way. Instead, they should be in a dialectical and even an affirmative relation. Employing deductive-descriptive method this article aims to reveal the discourse of Islam Nusantara on the aspects of universality of Islam and the cultural locality in Indonesia. Islam Nusantara is a sociological term for the manifestation of the universality of Islam which has been absorbed into the particularity of local cultures in Nusantara. The article will further argue that the encounter of Islam and the local cultures in Indonesia has created a uniquely indigenous model of understanding, comprehension, and practice of the Islamic doctrines. The notion of Islam Nusantara should, therefore, make the Indonesian Muslims able to synergize Islam and nationalism within a frame called ?Indonesia and diversity?.